Buya Hamka's Emancipatory Interpretation in Children's Education - Mansyur, Abd Rahim; Baharun, Hasan; Haslinda, Haslinda (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2022)
This paper aims to analyze and understand Buya Hamka's emancipatory interpretation of reasoning in children's education. This is because education is a place to accommodate skills and provide freedom for students; education is an effort to educate the nation's life. The researcher uses a qualitative approach to the type of library research. The results of this study indicate that the Koran is able to adapt subtly to the conditions of education in this era. Emancipatory interpretation can help humans in diagnosing and understanding the social problems of humanity faced by humanity. Emancipatory interpretation can be seen as a tool to sharpen conscience awareness in seeing, perceiving, and at the same time solving humanity's social problems.